The Javan Gibbon (Hylobates moloch) Habitat Changes and Fragmentation in the Dieng Mountains, Indonesia - Widyastuti, Salmah; Perwitasari-Farajallah, Dyah; Prasetyo, Lilik Budi; Iskandar, Entang (Institut Pertanian Bogor (IPB University), 2023)
The endangered javan gibbon (Hylobates moloch) has been threaten by massive habitat loss and fragmentation in Java. The survival of the second largest population which inhabited unprotected Dieng mountains faced greater risk to habitat conversion and fragmentation. The landscape-level habitat monitoring using spatiotemporal quantification is crucial as a baseline data for javan gibbon conservation. Here, the land-use and land-cover (LULC) change of the Javan gibbon habitat during 1994–2009–2021 and its fragmentation in the Dieng mountains were quantified. This study revealed there were no significant decline in the total of forest. However, its quality was degraded in the interior of forest block. The forest has more fragmented from large patches into smaller patches and increased forest edge. The higher fragmentation happened in the areas that traversed by road. Six suitable forest blocks were identified with varying level of connectivity. Protection and restoration both in the forest and in the interior forest is immediate need, especially in the main forest block. The extra effort is also crucial in the connected forest but traversed by road. The blocks which closely isolated by road could be potentially reconnected by artificial canopy bridge, while the other distantly isolated block might need habitat restoration for corridor.